MEDIATING ROLE OF DISSOCIATION SYMPTOMS BETWEEN ADOLESCENT COMPULSIVE INTERNET USE ACROSS TIME - Miltuze, Anika; Sebre, Sandra Beatrice (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of this study was to examine adolescent compulsive internet use (CIU) across a one-year period, to examine associations with symptoms of depression, anxiety and dissociation, as well as to analyze the potential mediating effect of dissociation symptoms. Previous studies have indicated that dissociation might serve as a coping strategy and/or as a consequence of problematic internet use. Participating in the study were 80 adolescents (39 girls and 41 boys), ages from 12 to 18 (mean age 14.90 years) at the time of the first measurement. At Time 1 and one year later at Time 2 measurement points the participants completed the Trauma Symptom Checklist (Briere, 1995) and items from the Compulsive Internet Use Scale (Meerkert, VanDen Eijnden, Vermulst, & Garretsen, 2009). Correlation analyses showed associations between CIU and the adolescents’ ratings of anxiety, depression and dissociation at Time 1 and Time 2. Mediation analysis indicated partial mediation of dissociation symptoms between CIU at Time 1 and Time 2. A comparison of these relationships across time provides opportunity to discuss possible directions of causality and implications of bidirectionality between dissociative tendencies and adolescent prolonged, compulsive internet use.